Unlocking the Economic Potential of Non-Timber Forest Products in Indonesia's Special Purpose Forest Zones - Hermudananto Hermudananto; Muhammad Navis Rofii; Sigit Sunarta; Ganis Lukmandaru; Ferrieren Curassavica Arfenda; Retno Nur Utami; Ananto Triyogo; Yeni Widyana Nurchahyani Ratnaningrum; Nunuk Supriyatno (The University of Lampung, 2025)
This study explores the diversity of Non-Timber Forest Products (NTFPs) in the Forest Zone with Special Purpose (KHDTK) of Getas-Ngandong, East Java, Indonesia, with the aim of optimizing resource allocation, livelihood diversification, and biodiversity conservation in its planning and management. By conducting a six-month (May–October 2018) biophysical survey through direct observation, coupled with structured social surveys and interviews with key informants in adjacent community-managed forest area. We identified a wide range of NTFPs that are critical for sustainable forest management. Understanding the diversity and distribution of NTFPs is necessary to inform strategic interventions that enhance forest sustainability while supporting the economic resilience of surrounding communities. The findings reveal a rich variety of NTFPs within the region, with agricultural and food crops such as corn, sugarcane, rice, and cassava prevalent inside forest areas, while fruits like mangoes and bananas dominate the surrounding non-forest areas. These insights can serve as valuable inputs, such as integrating fruit tree cultivation into agroforestry zones to enhance income stability, for developing a KHDTK management plan that diversifies income sources, supports local livelihoods, and promotes sustainable forest management practices by balancing economic, ecological, and social benefits. Keywords: Non-Timber Forest Products (NTFPs); Sustainable Forest Management; KHDTK Getas-Ngandong.